Presidential Election Polls in 2000: A Study in Dynamics. - Wlezien, Christopher (Presidential Studies Quarterly, 2003)
Much research shows that voters behave in understandable ways on election day and that election outcomes themselves are quite predictable. Even to the extent we can predict what voters do at the very end of the campaign, we know relatively little about how electoral preferences evolve over time. The U.S. presidential race in 2000 offers a fairly unique opportunity. The volume of available poll data for this particular election allows us to examine the dynamics of voter preferences in great detail for much of the election cycle. Analysis of the poll results in 2000 reveals that underlying electoral preferences changed quite meaningfully during the course of the campaign. The analysis also provides evidence that a significant portion of these changes in preferences actually persisted over time to affect the outcome on election day. Based on these results, it appears that the 2000 presidential election campaign mattered quite a lot. Reprinted by permission of the publisher.